Uso de la figura jurídica del testamento en el municipio de Neiva entre los años 2015 al 2018 (2020)
In the development of the current investigation, the historical evolution, the current regulations and in the same way the different forms of the protocolization of the will were analyzed, likewise, it was established that although said figure is in force, its application is of little use in Neiva.